Of injustice or justice? (Journal of Parents and Teachers, 2026)
It proposes a 67-point self-test designed to confront our attitudes towards social injustice, poverty and inequality. Through this test, the author questions indifference, consumerism and educational systems that ignore global poverty. It also offers a series of activities for parents and students to discuss and form real commitments to solidarity.
Keywords: Self-assessment, social injustice, debate and commitment.